RISING BRICS: A PATH TO MULTIPOLAR WORLD REALITY? - Shraddha Shrikant Naik (Сравнительная политика, 2018)
Abstract:The discourse over change in the world order from a unipolar to multipolar has gained major attention in the recent times. While the United States upholds the pivotal power position in the international system it has experienced relative economic decline in the recent periods. The economic growth among the countries of the Global South has led to their emergence as a new power contender in the international system. The grouping of Brazil, Russia, China, India, South Africa (BRICS) has firmly developed an interregional set up trying to add a new constellation in the world order. It has emerged as a new region of their own with certain shared similarities and common objectives. The group aims to create a niche in international system by creating supplementary intuitions. Adopting reformist attitude, the group stresses on the creation of a multipolar world order demanding recognition to the rising powers of the twenty-first century. The countries are asserting for expansion of the United Nations Security Council (UNSC), and reforms in the international financial institutions. The group has pioneered a new discourse of the Global South on the Responsibility while Protecting and Climate Change. However, the internal rivalries and recent slow growth of members leads to the speculation of the group in coordinating in its endeavour of multipolar world reality. Highlighting the BRICS as a new set of interregional interactions among the emerging powers, the paper while discussing the achievements and divergences of the grouping will assess its capability and efforts in creating a multipolar world order.